Features of clinical course of symptomatic focal epilepsy in children with hemiparetic cerebral palsy - V. M. Trepilets; L. G. Khachatryan; O. V. Bykova (Лечащий Врач, 2021)
The main causes of structural focal epilepsy in children with cerebral hemiparesis were defined. features of the treatment were clarified, as well as prognosis of epileptic attacks and the possibility of rehabilitation for children with this pathology.